2020
DOI: 10.21203/rs.2.23396/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Skeletal muscle loss in the postoperative acute phase after esophageal cancer surgery as a new prognostic factor

Abstract: Background: The postoperative survival rate of patients with esophageal squamous cell carcinoma (ESCC) remains poor compared with other gastrointestinal cancers. We hypothesized that skeletal muscle loss in the postoperative acute phase might be a new predictor for long-term prognosis after highly invasive surgery such as ESCC surgery.Methods: The following items were retrospectively investigated. First, whether skeletal muscle loss occurred in the postoperative acute phase of ESCC was verified. Second, the pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Compared to open gastrectomy, laparoscopic gastrectomy was associated with enhanced recovery of muscle mass at 6 months after surgery [45]. In addition, there were other studies revealing the protective effect of laparoscopic procedure on surgery-related muscle loss [26,46]. Furthermore, the current study found that serum albumin level on the 7th postoperative day was significantly lower in patients receiving open surgery.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Compared to open gastrectomy, laparoscopic gastrectomy was associated with enhanced recovery of muscle mass at 6 months after surgery [45]. In addition, there were other studies revealing the protective effect of laparoscopic procedure on surgery-related muscle loss [26,46]. Furthermore, the current study found that serum albumin level on the 7th postoperative day was significantly lower in patients receiving open surgery.…”
Section: Discussionmentioning
confidence: 47%
“…Similar to pancreatic cancer, in which a higher preoperative CA 19-9 was associated with surgical-related muscle loss [22], we have discovered that a more advanced HCC in terms of AFP or tumor size could also result in more pronounced muscle loss after surgery. Since disease severity is intrinsic to tumors and can hardly be altered, we should thus try to optimize the modifiable variables, i.e., adoption of laparoscopic approach and avoidance of major complications, to minimize skeletal muscle loss after surgery [24,26,46]. From the current study, significant muscle loss could impact not only the perioperative recovery but also the oncological outcome.…”
Section: Discussionmentioning
confidence: 92%
“…Esophageal cancer is one of the most common malignant tumors in the world [1]. Due to the complex anatomical structure of the esophagus and numerous lymph nodes involved in removal, the rate of postoperative recurrence and metastasis after surgery is high [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The well-documented occurrence of systemic inflammatory response syndrome (SIRS) after cardiac surgery, apart from its harmful action on the vascular endothelium, accelerates a profound endocrine-metabolic cascade that promotes hyper-catabolism [14][15][16][17], leading to skeletal muscle breakdown [4,18,19]. Although this hypercatabolic phase starts as early as the second postoperative day [14], in the short term, a wellnourished subject sustains minimal debilitation [19], to which, usually, no attention is paid, as long as the patient presents an uneventful postoperative course. However, this "uneventful" clinical outcome is commonly associated with measurable loss of muscle mass [4,18,19].…”
Section: Introductionmentioning
confidence: 99%